Dissociation method of high-roughness quartz sand
By adopting the crushing-grade scrubbing-grinding process in the pretreatment of quartz sand, the problems of excessive particle size and surface impurities in traditional processes are solved, and the yield and purity of quartz sand are improved.
Patent Information
- Application Number
- CN202411792625.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-07
AI Technical Summary
In the traditional quartz sand pretreatment process, the grinding process leads to excessive fine particle size, reducing the yield of qualified particle-grade quartz sand, and the surface of the quartz particles may still contain clay impurities and iron oxide films, affecting product quality.
The pretreatment process of crushing-classified scrubbing-grinding is adopted. Through high-concentration scrubbing and ultrasonic cavitation, the clay minerals and iron oxide film are separated from the quartz surface to ensure that the quartz sand reaches the monomer dissociation state.
The yield and ore dressing efficiency of quartz sand that meets standard particle size is significantly improved, ensuring high purity and low impurity content of quartz sand.
Smart Images

Figure CN119608357A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of quartz sand beneficiation, and in particular relates to a method for dissociating high-roughness quartz sand. Background Art
[0002] With the rapid development of semiconductor and photovoltaic industries, the demand for high-quality quartz raw materials has entered a stage where supply exceeds demand. With the increasing depletion of high-grade and high-purity quartz resources, such as crystal, the channels for obtaining high-purity quartz have gradually turned to relatively low-grade mineral resources such as pegmatite, vein quartz, quartzite and quartz sand, and the required high-purity quartz raw materials are extracted through complex purification technology. The field of high-purity quartz has very strict requirements on the quality of quartz sand, usually requiring the SiO2 content to be above 99.9% and the particle size to be within the range of -0.6+0.1mm.
[0003] Impurities in quartz ore mainly exist in the following forms: (1) mineral impurities with relatively high dissociation degree, including associated minerals, clay mineral impurities, etc.; (2) inclusion impurities; (3) structural impurities in the crystal lattice. The existence form of impurities in quartz ore determines the specific process of high-purity quartz purification in the later stage. Among them, the first type of impurities are non-structural impurities, which are relatively easy to remove. Usually, physical purification (such as magnetic separation, flotation, etc.) can achieve better impurity removal effect; while the second and third types are structural impurities, which usually need to be effectively removed by chemical purification or physical-chemical combined means.
[0004] Before physical and chemical purification, the raw ore needs to be crushed, ground and other pre-treatment processes to separate the quartz from the impurity mineral monomers, so that a good separation effect can be achieved in the subsequent ore dressing and purification links such as magnetic separation and flotation. The goal of the pre-treatment stage is to preliminarily screen impurities or to crush, grind and other means of quartz raw materials to achieve effective monomer dissociation of minerals and achieve the particle size required for subsequent processing. Quartz sand after pre-treatment usually needs to be further scrubbed, deslued and other treatments to remove iron oxides and clay substances adhering to the surface.
[0005] The traditional pretreatment process includes crushing, grinding (sometimes accompanied by scrubbing) and desludging. For those quartz sands with high degree of clay and iron oxide cementation and high surface roughness, since the embedded particle size of gangue minerals is usually fine, in order to achieve the monomer dissociation of quartz and gangue minerals, the grinding process often leads to too fine grinding particles, thereby reducing the yield of qualified quartz sand. In addition, the dissociation of quartz sand and surface adhering impurities after grinding is not complete, and the surface of quartz particles may still carry cemented clay impurities and iron oxide films. Because the particle size is fine, even if scrubbing is performed, the impurity removal effect is often unsatisfactory, which ultimately affects the quality of the product. Scrubbing uses mechanical force and friction between sand particles to remove film iron and adhesive impurities on the surface of quartz sand. However, during the scrubbing process, due to the unevenness of particle size, it is difficult to completely remove all surface impurities, which not only prolongs the scrubbing time but also reduces efficiency. Therefore, it is very important to develop an efficient dissociation method for quartz sand with high roughness, which will help to increase the output of quartz sand with standard particle size and the overall efficiency of mineral processing. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for dissociating high-roughness quartz sand. The present invention adopts a pretreatment process of crushing-grading scrubbing-grinding, and uses mechanical force to separate clay minerals and iron oxide films from the quartz surface through high-concentration scrubbing of the particle size. At the same time, the cavitation effect of ultrasound (introduced in the ultrasonic scrubbing step) is used to vibrate the slurry, accelerating the separation of quartz from surface impurity minerals such as clay and iron oxide. Compared with the traditional crushing-grinding-(scrubbing) desludging method, this new method fully guarantees the yield of qualified particle size quartz sand and improves the ore dressing efficiency.
[0007] The purpose of the present invention is achieved through the following technical solutions: A method for dissociating high-roughness quartz sand comprises the following steps: (1) Classify the quartz sand samples according to particle size; (2) The classified samples are respectively prepared into slurries, and a regulator and a dispersant are selectively added according to the properties of the quartz sand and then stirred; each slurry is then ultrasonically scrubbed until the slurry is neutral, filtered and dried to obtain materials of the corresponding particle size; (3) Screening the material with a particle size of -2mm+0.6mm to screen out quartz sand with a particle size of +0.6mm, and then grinding it to the required particle size according to the requirements of subsequent selection to obtain the first quartz sand sample; screening the material with a particle size of -0.6mm+0.1mm to screen out quartz sand with a particle size of +0.1mm to obtain the second quartz sand sample; the first quartz sand sample and the second quartz sand sample are quartz sand after monomer dissociation.
[0008] Preferably, in step (1), the particle size of the quartz sand sample is -2 mm + 0.1 mm.
[0009] Preferably, the step (1) is classified according to the particle size by: according to the sample particle size range, it is divided into -2mm+1mm particle size, -1mm+0.6mm particle size, -0.6mm+0.3mm particle size and -0.3mm+0.1mm particle size.
[0010] Preferably, in step (2), the concentration of the slurry is 60-70 wt %, and the stirring time is 5-10 min.
[0011] Preferably, in step (2), the stirring method is: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the stirring rate is 1600~2000rpm; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the stirring rate is 800~1300rpm.
[0012] Preferably, in step (2), the specific method of ultrasonically scrubbing each slurry is as follows: for samples of -2mm+1mm particle size and -1mm+0.6mm particle size, scrubbing is performed for 20-40 minutes at an ultrasonic frequency of 20-80KHz and an ultrasonic power of 500-600W; for samples of -0.6mm+0.3mm particle size and -0.3mm+0.1mm particle size, scrubbing is performed for 10-20 minutes at an ultrasonic frequency of 20-80KHz and an ultrasonic power of 500-600W.
[0013] Preferably, in step (2), the amount of the regulator added is specifically as follows: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the amount of the regulator added is 500~2000g / t; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the amount of the regulator added is 500~2000g / t.
[0014] Preferably, in step (2), the amount of dispersant added is specifically as follows: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the amount of dispersant added is 5000~15000 g / t; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the amount of dispersant added is 300~1000 g / t.
[0015] Preferably, in step (2), a regulator is added according to the properties of the quartz sand, and the regulator is an acidic or alkaline substance; specifically, an alkaline regulator, such as sodium hydroxide or sodium carbonate, is added to quartz sand containing organic matter; an acidic regulator, such as an inorganic acid such as hydrochloric acid or hydrofluoric acid, or an organic acid such as oxalic acid, is added to quartz sand with a high iron impurity content.
[0016] Preferably, in step (2), a dispersant is added according to the properties of the quartz sand. Specifically, a dispersant is added to the quartz sand with a high clay mineral content, and the dispersant is at least one of sodium hexametaphosphate, sodium pyrophosphate, sodium silicate, sodium citrate and sodium tripolyphosphate.
[0017] Preferably, in step (3), the first quartz sand sample and the second quartz sand sample are further purified to obtain quartz concentrate.
[0018] The mechanism involved in the present invention is: Monomer dissociation is the basic condition for quartz sand sorting and purification, and directly affects the subsequent sorting process and purification indicators. For quartz sand with high degree of clay and iron oxide cementation and high surface roughness, even after crushing, iron oxide and clay impurities may still adhere to the surface of quartz particles. Therefore, after classification, these impurities on the quartz surface are first removed by scrubbing, and then the coarse-grained samples (-2mm+1mm particle size and -1mm+0.6mm particle size) are ground to the appropriate particle size, which can significantly reduce the over-grinding phenomenon and increase the yield of qualified particle size quartz sand. At the same time, scrubbing narrow-grained samples (-0.6mm+0.3mm particle size and -0.3mm+0.1mm particle size) can enhance the scrubbing effect, make the grinding between quartz sand particles more sufficient, and remove impurities more thoroughly.
[0019] During the ultrasonic scrubbing process, the use of specific regulators and dispersants for quartz sands of different properties can enhance the removal of impurities. Under strong acidic conditions, most iron-containing impurity minerals will be dissolved, while quartz sand will not be dissolved; therefore, adding acid can effectively improve the removal of iron-containing impurity minerals. Alkaline agents are conducive to removing organic matter in quartz sand, and under alkaline conditions, the zeta potential of quartz and some gangue minerals (such as feldspar, hematite, etc.) is negative. By controlling the surface electrical properties of quartz and impurity minerals and increasing electrostatic repulsion, the removal effect of clay impurities can be improved. In addition, the use of dispersants can significantly reduce the viscosity of the slurry and increase the recovery rate of quartz, especially for quartz sands with a high content of clay minerals. The cavitation, mechanical and thermal effects of ultrasound help remove impurities and iron oxide films deposited and adsorbed on the surface of quartz sand, thereby enhancing the monomer dissociation effect.
[0020] Compared with the prior art, the beneficial effects of the present invention include: (1) For high-roughness quartz sand, the pretreatment process of "crushing-grading scrubbing-grinding" can make quartz more efficiently dissociate monomers. The scrubbing process before grinding can pre-dissociate impurity minerals, and then the required quartz particle size range can be obtained through grinding, thereby minimizing the over-grinding of quartz sand caused by the dissociation of impurity minerals and ensuring the yield of quartz sand of qualified particle size.
[0021] (2) Ultrasonic scrubbing of narrow particle sizes is more efficient than scrubbing of mixed particle sizes, and the grinding between the sand and gravel is more thorough. At the same time, under the cavitation effect of ultrasound, the dissociation of iron oxide and impurity minerals on the quartz surface is more complete. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the quartz sand dissociation process of the present invention and the traditional method, wherein the left figure corresponds to the traditional method and the right figure corresponds to the method of the present invention.
[0023] Figure 2 It is a schematic diagram comparing the effects of the narrow-size scrubbing method of the present invention and the traditional mixed scrubbing method. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] Example 1 A method for dissociating high-roughness quartz sand, the steps are as follows: (1) Quartz sand from Dongshan, Fujian Province was selected. The -0.6mm+0.1mm particle size accounted for 97.21% of the quartz sand, which met the requirements for the particle size of glass sand. Therefore, no crushing and grinding process was required. The material was screened into -0.6mm+0.3mm particle size and -0.3mm+0.1mm particle size by standard wet screening.
[0026] (2) Using deionized water, the materials of -0.6mm + 0.3mm particle size and -0.3mm + 0.1mm particle size were respectively prepared into slurries with a concentration of 60%, and NaOH solution (concentration of 1%) was added to each according to the standard of 500g / t and then stirred. Specifically, the material of -0.6mm + 0.3mm particle size was stirred at a rate of 1000rpm for 5min, and the material of -0.3mm + 0.1mm particle size was stirred at a rate of 800rpm for 5min. After stirring, each slurry was ultrasonically scrubbed. Specifically, the samples of -0.6mm + 0.3mm particle size and -0.3mm + 0.1mm particle size were scrubbed at an ultrasonic frequency of 40KHz and an ultrasonic power of 550W for 20min. After the ultrasonic scrubbing is completed, deionized water is used to wash the ore pulp until it is neutral, and then filtered and dried to obtain materials of corresponding particle sizes; the materials of corresponding particle sizes are mixed to obtain quartz sand after monomer dissociation.
[0027] (3) The quartz sand after monomer dissociation was subjected to three-stage magnetic separation, with a magnetic separation intensity of 1.4 T, a pulse frequency of 200 r / min, and a flow rate of 2.0 cm / s. The magnetic separation concentrate was then acid-leached under the following conditions: temperature 80°C, acid type 10wt% oxalic acid solution plus 1wt% hydrofluoric acid solution, liquid-solid ratio 1mL:1g, and acid leaching time 8h. After acid leaching, the sample was washed to neutrality to obtain quartz concentrate.
[0028] The quartz concentrate described in Example 1 was subjected to ICP detection, and the iron oxide content was 105 μg / g, the aluminum oxide content was 4023 μg / g, and the quartz concentrate yield was 94.56%.
[0029] Comparative Example 1 A method for dissociating quartz sand, the steps are as follows: (1) Quartz sand from Dongshan area of Fujian Province was selected. The -0.6mm+0.1mm particle size ratio of this quartz sand was 97.21%, which met the particle size requirements for glass sand. Therefore, no crushing and grinding process was required.
[0030] (2) Deionized water was used to prepare the -0.6mm +0.1mm particle size material into a 60% slurry, and NaOH solution (concentration of 1%) was added to each according to the standard of 500g / t, and then stirred at a speed of 1000rpm for 5 minutes. After the stirring, the slurry was ultrasonically scrubbed at a frequency of 40KHz, a power of 550W, and a scrubbing time of 20 minutes. After the ultrasonic scrubbing was completed, the slurry was washed with deionized water until it was neutral, filtered and dried to obtain quartz sand after monomer dissociation.
[0031] (3) According to the method of Example 1, the quartz sand after monomer dissociation is subjected to magnetic separation and acid leaching to obtain quartz concentrated sand.
[0032] The quartz concentrate described in Comparative Example 1 was subjected to ICP detection, and the iron oxide content was 127 μg / g, the aluminum oxide content was 4916 μg / g, and the quartz concentrate yield was 90.28%.
[0033] Example 2 A method for dissociating high-roughness quartz sand, the steps are as follows: (1) Quartz ore from Shimen, Hunan Province was selected for crushing. After a closed-circuit crushing process, the experimental quartz sandstone was crushed to less than 3 mm, and then crushed by rollers. The crushing fineness was +0.1 mm and the yield was 90%. The +0.1 mm quartz sand (qualified quartz sand) was taken for standby. The +0.1 mm quartz sand was sieved by wet screening and divided into three quartz sands: +0.6 mm, -0.6 mm + 0.3 mm, and -0.3 mm + 0.1 mm.
[0034] (2) Use deionized water to prepare a 60% slurry, add a regulator and a dispersant, stir for 5 minutes, and then perform ultrasonic scrubbing. Specifically: For the +0.6mm particle size material, add NaOH solution (concentration of 3%) according to the standard of 500g / t, and add sodium hexametaphosphate solution (concentration of 10%) according to the standard of 5000g / t, and stir at a rate of 1600rpm; the frequency of ultrasonic scrubbing is 40KHz, the power is 550W, and the scrubbing time is 25min; the scrubbed quartz sand is washed with deionized water until the water is clear, filtered and dried. The +0.6mm particle size material after ultrasonic scrubbing is ground, the grinding concentration is 60%, the grinding medium is rod mill, the grinding fineness is -0.6mm +0.1mm particle size content is 80%, and after grinding, the -0.6mm +0.1mm particle size product is screened and graded for standby use, recorded as quartz sand sample 1; For the material of -0.6mm+0.3mm particle size, NaOH solution (concentration of 1.5%) and sodium hexametaphosphate solution (concentration of 1.5%) were added according to the standard of 500g / t, and the stirring rate was 1000rpm; the frequency of ultrasonic scrubbing was 40KHz, the power was 550W, and the scrubbing time was 20min; the scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried; recorded as quartz sand sample 2; For materials with a particle size of -0.3mm+0.1mm, add NaOH solution (concentration of 1.5%) and sodium hexametaphosphate solution (concentration of 1.5%) according to the standard of 500g / t, respectively, and stir at a rate of 800rpm; the frequency of ultrasonic scrubbing is 40KHz, the power is 550W, and the scrubbing time is 20min. The scrubbed quartz sand is washed with deionized water until the water is clear, filtered and dried. Recorded as quartz sand sample three; The quartz sand sample one, the quartz sand sample two and the quartz sand sample three are mixed to obtain quartz sand after monomer dissociation.
[0035] (3) The quartz sand after monomer dissociation was subjected to three-stage magnetic separation. The magnetic separation medium was a fine steel rod, the magnetic separation intensity was 1.4 T, the pulse frequency was 200 r / min, and the flow rate was 1.0 cm / s. Then the magnetic separation concentrate was acid leached. The acid leaching conditions were: temperature 85°C, acid type 10wt% oxalic acid solution plus 1wt% hydrofluoric acid solution, liquid-solid ratio 1mL:1g, and acid leaching time 6h. After acid leaching, the sample was washed to neutral to obtain quartz concentrate.
[0036] The quartz concentrate described in Example 2 was subjected to ICP detection, and the iron oxide content was 82.43 μg / g, the aluminum oxide content was 478.24 μg / g, and the quartz concentrate yield was 82.21%.
[0037] Comparative Example 2 A method for dissociating quartz sand, the steps are as follows: (1) Quartz ore was selected from Shimen, Hunan Province, and the large blocks of quartz sandstone used in the experiment were crushed to less than 3 mm through a closed-circuit crushing process. The crushed materials were ground with a grinding concentration of 60%. The grinding medium was a rod mill, and the grinding fineness was -0.6 mm + 0.1 mm. The content of the particle size was 80%. After grinding, the -0.6 mm + 0.1 mm particle size product was screened out for standby use.
[0038] (2) Using deionized water, the material of -0.6mm +0.1mm particle size was prepared into a 60% slurry, and NaOH solution (concentration of 1.5%) and sodium hexametaphosphate solution (concentration of 1.5%) were added according to the standard of 500g / t, and then stirred at a speed of 1000rpm for 5 minutes. After stirring, the slurry was ultrasonically scrubbed at a frequency of 40KHz, a power of 550W, and a scrubbing time of 20 minutes. After the ultrasonic scrubbing was completed, the slurry was washed with deionized water until it was neutral, filtered and dried to obtain quartz sand after monomer dissociation.
[0039] (3) According to the method of Example 2, the quartz sand after monomer dissociation is subjected to magnetic separation and acid leaching to obtain quartz concentrated sand.
[0040] The quartz concentrate described in Comparative Example 2 was subjected to ICP detection, and the iron oxide content was 94.04 μg / g, the aluminum oxide content was 569.25 μg / g, and the quartz concentrate yield was 71.05%.
[0041] Example 3 A method for dissociating high-roughness quartz sand, the steps are as follows: (1) Select Angola quartz ore for crushing. After a closed-circuit crushing process, the experimental quartz sandstone blocks are crushed to less than 3 mm, and then crushed by rollers. The crushing fineness is -2mm+0.1mm particle size yield 95%. Take +0.1mm particle size quartz sand (qualified particle size) for standby use. Through wet screening, the +0.1mm particle size quartz sand is divided into four particle sizes of -2mm+1mm, -1mm+0.6mm, -0.6mm+0.3mm, and -0.3mm+0.1mm using standard screening.
[0042] (2) Use deionized water to prepare a 65% slurry, add a regulator and a dispersant, stir for 5 minutes, and then perform ultrasonic scrubbing. Specifically: For materials with a particle size of -2mm+1mm, oxalic acid solution (concentration of 1%) was added at a standard of 500g / t, and the stirring rate was 1800rpm; the frequency of ultrasonic scrubbing was 40KHz, the power was 550W, and the scrubbing time was 25min; the scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried; For materials with a particle size of -1mm+0.6mm, oxalic acid solution (concentration of 1%) was added at a standard of 500g / t, and the stirring rate was 1600rpm; the frequency of ultrasonic scrubbing was 40KHz, the power was 550W, and the scrubbing time was 20min; the scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried; The -2mm+1mm and -1mm+0.6mm grade materials after scrubbing and washing are mixed and ground, the grinding concentration is 60%, the grinding medium is a rod mill, the grinding fineness is -0.6mm+0.1 mm grade content is 80%, after grinding, the -0.6mm+0.1 mm grade product is screened out for standby use, recorded as sample 1; For the -0.6mm+0.3mm particle size materials, oxalic acid solution (concentration of 1%) was added at a standard of 500g / t, and the stirring rate was 1000rpm; the frequency of ultrasonic scrubbing was 40KHz, the power was 550W, and the scrubbing time was 15min. The scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried, and recorded as sample 2; For the -0.3mm+0.1mm particle size materials, oxalic acid solution (concentration of 1%) was added according to the standard of 500g / t, and the stirring rate was 800rpm; the frequency of ultrasonic scrubbing was 40KHz, the power was 550W, and the scrubbing time was 15min. The scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried, and recorded as sample three; Sample 1, sample 2 and sample 3 are mixed to obtain quartz sand after monomer dissociation.
[0043] (3) The quartz sand after monomer dissociation was subjected to two-stage flotation to remove mica, with a flotation concentration of 30%. The flotation reagent used was dodecylamine, with a dosage of 100 g / t per stage, and HF was used to control the pH to 2.0-3.0. The concentrate after flotation was acid-leached using a 4wt% hydrofluoric acid solution, a solid-liquid volume ratio of 1:3, an acid-leaching time of 24 h, and an acid-leaching temperature of 90°C. After acid-leaching, the sample was washed to neutrality, filtered, and dried to obtain quartz concentrate.
[0044] The quartz concentrate described in Example 3 was subjected to ICP detection, and the iron content was 0.28 μg / g, the aluminum content was 15.51 μg / g, and the quartz concentrate yield was 80.35%.
[0045] Comparative Example 3 A method for dissociating quartz sand, the steps are as follows: (1) Angola quartz ore was selected for crushing. After a closed-circuit crushing process, the experimental quartz sandstone blocks were crushed to less than 3 mm, and then crushed by rollers. The crushing fineness was -2mm+0.1mm and the yield was 95%. The +0.1mm quartz sand (qualified particle size) was taken for standby use. The crushed material was ground with a grinding concentration of 60%, a rod mill as the grinding medium, a grinding fineness of -0.6mm +0.1 mm and a particle size content of 80%. After grinding, the -0.6mm +0.1 mm particle size product was screened out for standby use.
[0046] (2) Deionized water was used to prepare the -0.6mm +0.1mm particle size material into a 60% slurry, and oxalic acid solution (concentration of 1%) was added to each of them according to the standard of 500g / t, and then stirred at a speed of 1000rpm for 5 minutes. After stirring, the slurry was ultrasonically scrubbed at a frequency of 40KHz, a power of 550W, and a scrubbing time of 15 minutes. The scrubbed quartz sand was washed with deionized water until the water was clear, filtered and dried to obtain quartz sand after monomer dissociation.
[0047] (3) The quartz sand after monomer dissociation is subjected to flotation and acid leaching according to the method of Example 3 to obtain quartz concentrate.
[0048] The quartz concentrate described in Comparative Example 3 was subjected to ICP detection, and the iron content was 0.43 μg / g, the aluminum content was 16.25 μg / g, and the yield of quartz concentrate was 76.21%.
[0049] The ICP test results of the quartz concentrates prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.
[0050] Table 1 Comparison of ICP test results of quartz concentrate
[0051] According to the test results in Table 1, it can be seen that the selective grinding after narrow particle size ultrasonic scrubbing according to the present invention can improve the qualified particle size yield of quartz concentrate and optimize the dissociation effect. Compared with the traditional crushing-grinding-scrubbing dissociation method, this method can obtain quartz sand concentrate with lower impurity content and higher yield.
[0052] Figure 1 Schematic diagram of the quartz sand dissociation process of the present invention and the traditional method, wherein the left figure corresponds to the traditional method and the right figure corresponds to the method of the present invention.
[0053] Figure 2 It is a schematic diagram comparing the effects of the narrow-size scrubbing method of the present invention and the traditional mixed scrubbing method.
[0054] from Figure 1~2 It can be seen that in the traditional quartz sand dissociation method, the sample is not classified after grinding, but the materials of various particle sizes are mixed and scrubbed, so the quartz sand obtained by scrubbing still contains a lot of impurities. However, the classification scrubbing method described in the present invention can make quartz more efficiently realize monomer dissociation.
[0055] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for dissociating high-roughness quartz sand, characterized in that: The steps include: (1) Classify the quartz sand samples according to particle size; (2) The classified samples are respectively prepared into slurries, and a regulator and a dispersant are selectively added according to the properties of the quartz sand and then stirred; each slurry is then ultrasonically scrubbed until the slurry is neutral, filtered and dried to obtain materials of the corresponding particle size; (3) Screening the material with a particle size of -2mm+0.6mm to screen out quartz sand with a particle size of +0.6mm, and then grinding it to the required particle size according to the requirements of subsequent selection to obtain the first quartz sand sample; screening the material with a particle size of -0.6mm+0.1mm to screen out quartz sand with a particle size of +0.1mm to obtain the second quartz sand sample; the first quartz sand sample and the second quartz sand sample are quartz sand after monomer dissociation.
2. The method for dissociating high-roughness quartz sand according to claim 1, characterized in that: The particle size of the quartz sand sample in step (1) is -2mm+0.1mm.
3. The method for dissociating high-roughness quartz sand according to claim 2, characterized in that: The method of classifying according to particle size in step (1) is as follows: according to the particle size range of the sample, the particles are classified into -2 mm + 1 mm particle size, -1 mm + 0.6 mm particle size, -0.6 mm + 0.3 mm particle size and -0.3 mm + 0.1 mm particle size.
4. The method for dissociating high-roughness quartz sand according to claim 1, characterized in that: The concentration of the slurry in step (2) is 60-70 wt %, and the stirring time is 5-10 min.
5. The method for dissociating high-roughness quartz sand according to claim 3, characterized in that: The stirring method in step (2) is: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the stirring rate is 1600~2000rpm; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the stirring rate is 800~1300rpm.
6. The method for dissociating high-roughness quartz sand according to claim 5, characterized in that: The specific method of ultrasonically scrubbing each slurry in step (2) is as follows: for samples of -2mm+1mm particle size and -1mm+0.6mm particle size, scrubbing is performed for 20-40 minutes at an ultrasonic frequency of 20-80KHz and an ultrasonic power of 500-600W; for samples of -0.6mm+0.3mm particle size and -0.3mm+0.1mm particle size, scrubbing is performed for 10-20 minutes at an ultrasonic frequency of 20-80KHz and an ultrasonic power of 500-600W.
7. The method for dissociating high-roughness quartz sand according to claim 6, characterized in that: The amount of the regulator added in step (2) is specifically as follows: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the amount of the regulator added is 500~2000g / t; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the amount of the regulator added is 500~2000g / t.
8. The method for dissociating high-roughness quartz sand according to claim 7, characterized in that: The specific amount of the dispersant added in step (2) is: for samples with a particle size of -2mm+1mm and -1mm+0.6mm, the amount of the dispersant added is 5000~15000 g / t; for samples with a particle size of -0.6mm+0.3mm and -0.3mm+0.1mm, the amount of the dispersant added is 300~1000 g / t.
9. The method for dissociating high-roughness quartz sand according to any one of claims 1 to 3, characterized in that: The regulator in step (2) is an acidic or alkaline substance; The alkaline substance is at least one of sodium hydroxide and sodium carbonate; The acidic substance is at least one of an organic acid and an inorganic acid; The dispersant is at least one of sodium hexametaphosphate, sodium pyrophosphate, sodium silicate, sodium citrate and sodium tripolyphosphate.
10. The method for dissociating high-roughness quartz sand according to claim 1, characterized in that: Step (3) The first quartz sand sample and the second quartz sand sample are further purified to obtain quartz concentrate.
Citation Information
Patent Citations
Method for preparing ultra-white glass material by purifying fine-grained quartz sandstone
CN112619883A
Method for efficiently and comprehensively utilizing low-quality calcium magnesium quartzite ore
CN117753555A
Purification method of quartz ore mixed with ultrafine mica
CN117983399A
Glass / quartz composite surface
US20200002214A1
Process for treating contaminated soil
US5115986A